Eqbal Ahmad : Critical Outsider in a Turbulent Age - Schaar, Stuart (Karachi Oxford Univ. Press, 2015)
Eqbal Ahmad was a bold and original activist, journalist and theorist who brought uncommon perspective to the rise of militant Islam, the conflict in Kashmir, the involvement of the United States in Vietnam and the geopolitics of the Cold War. A long-time friend and intellectual collaborator of Ahmad, Stuart Schaar presents in this book previously unseen materials by and about his colleague, having travelled through the United States, India, Pakistan, Western Europe and North Africa to connect Ahmad's experiences to the major currents of modern history.
Include Illustration, Bibliography and Index
Keywords: Political activists -- Social change -- World politics